PALB2 jako další kandidátní gen pro genetické testování u pa-cientů s hereditárním karcinomem prsu v České republice - Janatová, M; Borecká, M; Soukupová, J; Kleiblová, P; Stříbrná, J; Vočka, M; Zemánková, P; Panczak, A; Veselá, K; Souček, P; Foretová, L; Kleibl, Z (Klinicka onkologie, 2016)
BACKGROUND: The PALB2 (FANCN) gene was identified as a component of endogenous BRCA2 complex that encodes a DNA repair protein participating along with BRCA1 and BRCA 2 proteins in DNA double-strand break repair. Hereditary PALB2 mutations are associated with an increased risk of breast and pancreatic cancers in heterozygotes. Breast cancer risk for PALB2 mutation carriers has recently been estimated at 33-58% depending on family history of breast cancer; pancreatic cancer risk in carriers of PALB2 mutations has not been precisely quantified, yet. MATERIALS AND RESULTS: Results of a study identifying PALB2 mutations in high-risk, BRCA1/2-negative, breast and/or ovarian cancer patients in the Czech Republic indicate that the frequency of hereditary PALB2 mutations in our population is quite high. Interestingly, almost 20% of all recognized mutations comprised large genomic rearrangements. The highest proportion of PALB2 mutations (comparable with the number of mutations reported for BRCA2) was found in a subgroup of hereditary breast cancer patients (5.5%). Frequency of mutations in an independent group of Czech unselected pancreatic cancer patients was approximately 1.3%. CONCLUSION: Considering the frequency of pathogenic, hereditary PALB2 mutations in our population, their phenotypic similarity to BRCA2, and expected risk of breast cancer associated with PALB2 mutations, its screen-ing (including large genomic rearrangements) should be encouraged in patients from hereditary breast cancer families. The follow-up of pathogenic PALB2 mutation carriers should be similar to that in BRCA2 mutation carriers, enabling early diagnosis, prevention, and possible targeted therapy. Preventive surgical interventions for the carriers could be considered in case of strong family cancer history and evident segregation of a pathogenic mutation with a tumor phenotype. Additional analysis of various cancer patient populations and further meta-analyses will be necessary for accurate assessment of PALB2 gene penetrance and its significance for the risk of pancreatic and other cancers.
Keywords: Tumor Suppressor Proteins; nádorové supresorové proteiny; nádory prsu; protein FANCN; Female; mutace; Fanconi Anemia Complementation Group N Protein; genetické testování; Breast Neoplasms; Genetic Testing; ženské pohlaví; jaderné proteiny; Humans; Mutation; lidé; Nuclear Proteins